Partially Thrombosed Internal Maxillary Pseudoaneurysm after Gunshot Wound. Issue 4 (December 2016) - Gold, Menachem
A 29-year-old man arrived in our emergency department after being shot on the face. Computed tomography (CT) revealed multiple facial bone fractures along the bullet trajectory. On day 10 of admission, CT angiogram of the neck revealed a partially thrombosed pseudoaneurysm in the parapharyngeal fat pad. The pseudoaneurysm was successfully treated with coil embolization. This report discusses diagnosis and treatment of a partially thrombosed internal maxillary artery pseudoaneurysm. Although digital subtraction angiography is the gold standard for pseudoaneurysm diagnosis, CT angiography may provide complimentary information, as seen in this case.